COMPUTATION CHEZY’S COEFFICIENT IN A SEMI-ELLIPTICAL PIPE - Beboukha, Y.; Lakehal, M.; Remaoun, M.; Ghomri, A.; Achour, B. (Journal of Fundamental and Applied Sciences, 2019)
In the hydraulic field, the Chezy’s flow resistance coefficient in canals and pipes is often chosen arbitrarily. This value is tabulated independently of the depth of the flow or hydraulic radius and even less of the Reynolds number. This coefficient is usually influenced by a number of parameters that must be defined and considered. The objective of this study is to examine, on the one hand, the variation of the Chezy’s flow resistance coefficient for a semi-elliptical pipe under the hypothesis of an uniform flow with free surface, and to determine on the other hand, the expressions which govern them. Further, it must search expression for Chezy’s with consideration of the geometric characteristics of the pipe and hydraulic flow. This study is based on the rough model method (RMM).